Mechanical vibrations : theory and applications - Kelly, S. Graham (Mason, OH : South-Western, Cengage Learning, 2012)
Takes an applications-based approach at teaching students to apply previously learned engineering principles while laying a foundation for engineering design. This text offers a review of the principles of dynamics so that terminology and notation are consistent and applies them to derive mathematical models of dynamic mechanical systems.
1. Introduction. 2. Modeling of sdof systems. 3. Free vibrations of sdof systems. 4. Harmonic excitation of sdof systems. 5. Transient vibrations of one-degree-of-freedom systems. 6. Two-degree of freedom systems. 7. Modeling of mdof systems. 8. Free vibrations of mdof systems. 9. Forced vibratiobs of mdof systems. 10. Vibrations of continuous systems. 11. Finite element method. 12. Nonlinear vibrations. 13. Random vibrations. APPENDIX A. Unit impulse function and unit step function. APPENDIX B. Laplace transforms. APPENDIX C. Linear algebra. APPENDIX D. Deflections of beams due to concentrated loads. APPENDIX E. Matlab programs.
Includes bibliographical references (p. 851-852) and index.
Keywords: Vibration -- Textbooks